Keragaman fitoplankton di perairan estuaria Kuala Gigieng Kabupaten Aceh Besar, Provinsi Aceh - Fahni Sarinda; Irma Dewiyanti (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2013)
Abstract. The objective of the present study was to evaluate diversity of phytoplankton as bioindicator water quality viewed from abundance, diversity index, evenness index, and saphrobic coefficient in Kuala Gigieng, Aceh Besar District, Aceh Province. Sampling was conducted on December 2011 to January 2012. This study applied purposive sampling method. The research obtained 4 families consisted of Crysopyceae (42 genera), Chlorophyceae (8 genera), Cyanophyceae (14 genera) and Euglenophyceae (4 genera). The highest abundance of phytoplankton was 1,362.89 ind/l at high tide on station 3 and the lowest was at low tide on station 1 (809,835 ind/l). The diversity index (H’) was ranged from 3.14 to 4.75, the evenness index (E) was ranged from 0.49 to 0.74, and saprobic coefficient was ranged from 0.331to 0.887. Based on saprobic coefficient, pollution level and water quality was categorized light to moderate level. Furthermore, phase of saprobic were β-mesosaprobik, β-meso/Oligosaprobik dan β/α-mesosaprobik.Key words : phytoplankton, abundance, diversity index, saprobic coefficient.